Pengaruh Literasi Keuangan, Inklusi Keuangan, dan E-Commerce Terhadap Kinerja UMKM Sektor Kuliner di Kecamatan Denpasar Barat - Fatmawati Fatmawati; Sudarsana Arka (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
This study aims to analyze the influence of financial literacy, financial inclusion, and e-commerce utilization on the performance of Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector operating in West Denpasar District. The background of this study is based on the strategic role of MSMEs in supporting the local economy, particularly in creating jobs and increasing community income. However, amid the dynamics of the digital economy and recovery efforts after the COVID-19 pandemic, MSMEs face new challenges that require adaptation in business management, particularly related to financial literacy and the use of technology. This study uses a quantitative approach with data collection techniques through distributing questionnaires to 100 culinary MSME respondents in the study area. The research instrument focused on measuring the level of financial literacy, access to financial services (inclusivity), and the use of e-commerce platforms in daily business activities. The collected data were analyzed using multiple linear regression methods preceded by classical assumption tests to ensure model validity. The results show that simultaneously, all three independent variables—financial literacy, financial inclusion, and e-commerce—have a significant influence on MSME performance. Partially, financial literacy and e-commerce have a positive and significant impact on improving business performance. Meanwhile, financial inclusion does not show a significant effect individually, although it remains important in the context of financial service accessibility. These findings underscore the importance of improving financial literacy and utilizing digital technology in boosting the productivity and sustainability of MSMEs, particularly in the culinary sector. Therefore, ongoing policy support and training are needed to help MSMEs face the challenges of the digital economy more adaptively and competitively. Considering these findings, collaboration between local governments, financial institutions, and digital platforms is key to creating a conducive business ecosystem.